Gold‐Catalyzed Synthesis of Tetrazoles from Alkynes by CC Bond Cleavage1. Issue 50 (13th November 2013) - Gaydou, Morgane; Echavarren, Antonio M.
<x xml:space="preserve">Abstract</x> Golden duality: Tetrazoles are formed by the reaction of alkynes with TMSN3 (TMS=trimethylsilyl) in the presence of iPrOH and the gold(I) catalyst [JohnPhosAu(MeCN)]SbF6. In this transformation gold plays a dual role, first activating the alkyne and then generating a Brønsted acid in situ.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>